2006
DOI: 10.1557/jmr.2006.0304
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phase relations in the Co–Cu–Ti system by the diffusion triple technique

Abstract: Two isothermal sections of the Co–Cu–Ti ternary system at 973 and 1123 K were experimentally determined using the diffusion triple technique together with scanning electron microscopy and electron probe microanalysis. The solubility of Cu (substituting Co) in CoTi increased from 22.8 at.% at 973 K to 28.1 at.% at 1123 K while that of Co (substituting Cu) in CuTi decreased from 11.1 to 8.8 at.% accordingly. In addition, the solubility limits of the third element in the binary compounds CoTi2, CuTi2, Cu4Ti3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…Note here that this deducibility is based on the assumption that there are no other new phases appearing within the temperature and composition range involved. Although, Ti 33 Co 10 Cu 57 was reported by Pfeifer et al [5] using X-ray diffraction, however, this ternary phase was not found in the present work and our previous experiments [6]. We cannot rule out the possibility that this reported ternary compound is real, but it did not form in our diffusion triples.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Note here that this deducibility is based on the assumption that there are no other new phases appearing within the temperature and composition range involved. Although, Ti 33 Co 10 Cu 57 was reported by Pfeifer et al [5] using X-ray diffraction, however, this ternary phase was not found in the present work and our previous experiments [6]. We cannot rule out the possibility that this reported ternary compound is real, but it did not form in our diffusion triples.…”
Section: Discussioncontrasting
confidence: 70%
“…We shall now compare the observed phase relations in the isothermal section at 923 K with our previous work at 973 K [6] and see if any phase reactions can be identified in the Co-Cu-Ti system between 923 and 973 K. First, the three-phase equilibria #10, #11 and #12 in this isothermal section are consistent with our previous work at 973 and 1123 K. And this area including #10, #11 and #12 is wellinosculated with the work of Pfeifer et al [5] too. Second, there are several three-phase equilibria at both temperatures involving four phases: CoTi, CuTi, Cu 4 Ti 3 and Cu 3 Ti 2 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They suggested that the formation of the CuTi 3 phase was controlled by the annealing temperature and annealing time. At the same time, it should be a metastable phase in light of the works carried out by the other groups (Massalski et al, 1986;Xu et al, 2005;Liu et al, 2006a;Wang et al, 2006) a) Author to whom correspondence should be addressed. Electronic mail: zyzmatres@163.com…”
Section: A Cu-ti Binary Systemmentioning
confidence: 99%
“…Cu 4 Ti, Cu 3 Ti 2 , Cu 4 Ti 3 , CuTi and CuTi 2 . Although Canale and Servant [6] recently suggested that CuTi 3 is a stable phase on the basis of their experimental results, it should be a metastable phase in light of the works carried out subsequently by the other groups [7][8][9]. In the Ti-Sn phase diagram, four binary compounds, namely Ti 3 Sn, Ti 2 Sn, Ti 5 Sn 3 and Ti 6 Sn 5 , were reported in Ref.…”
Section: Introductionmentioning
confidence: 99%